Performance of electron and photon triggers in ATLAS during LHC Run 2 - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (The European physical journal. C, Particles and fields, 2020)
Electron and photon triggers covering transverse energies from 5 GeV to several TeV are essential for the ATLAS experiment to record signals for a wide variety of physics: from StandardModel processes to searches for new phenomena in both proton-proton and heavy-ion collisions. To cope with a fourfold increase of peak LHC luminosity from 2015 to 2018 (Run 2), to 2.1 x 10(34) cm(-2) s(-1), and a similar increase in the number of interactions per beam-crossing to about 60, trigger algorithms and selections were optimised to control the rates while retaining a high efficiency for physics analyses. For proton-proton collisions, the single-electron trigger efficiency relative to a single-electron offline selection is at least 75% for an offline electron of 31 GeV, and rises to 96% at 60 GeV; the trigger efficiency of a 25GeVleg of the primary diphoton trigger relative to a tight offline photon selection is more than 96% for an offline photon of 30 GeV. For heavy-ion collisions, the primary electron and photon trigger efficiencies relative to the corresponding standard offline selections are at least 84% and 95%, respectively, at 5 GeV above the corresponding trigger threshold.
ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, L. Henkelmann, J. Jongmanns, M. Klassen, A. Krishnan, A. Kugel, K. Mkrtchyan, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schöning, H.-C. Schultz--Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S.M. Weber, M. Wessels, X. Yue und 2898 weitere
Gesehen am 16.04.2020